Kesejahteraan Masyarakat Perbatasan Sebagai Tolak Ukur Efektivitas Keadilan di Indonesia - Gede Yudiarta Wiguna; Siti Safa’ati Rohmah; Gusti Ayu Indira Syahrani Putri (Universitas Pendidikan Ganesha, 2020)
This article was written with the aim of discussing the situation of the people who live on the borders of the Unitary State of the Republic of Indonesia, which are classified as far from the reach of the government regarding justice and justice. The lack of concern for the conditions of life in the border region is a rebellion which has an effect on the sense or spirit of people's nationalism towards their own homeland. The method used in this article is a case study type qualitative approach. This article explains the definition of justice obtained from accountable sources and in this article discusses the conditions and situations of the people who live in the border area as a measure for the realization of equitable justice and justice. This article can later be used as a reference in realizing the welfare and justice of communities in border areas.